Working the edges of Posthuman disability studies: theorising with disabled young people with life‐limiting impairments. Issue 8 (7th June 2019) - Liddiard, Kirsty; Whitney, Sally; Evans, Katy; Watts, Lucy; Vogelmann, Emma; Spurr, Ruth; Aimes, Carrie; Runswick‐Cole, Katherine; Goodley, Dan
Abstract: This paper is built upon an assumption: that social theory can be generated through a meaningful engagement with a co‐researcher group of disabled young people. Our co‐researchers are theoretical provocateurs and theorists in their own right who, through their activism and writing, are challenging us to reconsider the meaning of life, death and disability. Their work on our funded Economic and Social Research Council (ESRC) project has enabled us to consider the promise and potential of humanist and posthuman epistemologies, theories, methodologies, interventions and activisms. The paper introduces the research, the authors of this paper (academics and co‐researchers) and then explores three layers of analysis that work the edges of posthuman thinking; sovereign and assembled selves; affects and desires; mourning and affirmation. We conclude by asserting that as a research team we are engaging with a DisHuman approach to theory and activism: one that blends the pragmatics of humanism with posthuman possibilities.